CHI '13 Extended Abstracts on Human Factors in Computing Systems 2013
DOI: 10.1145/2468356.2479541
|View full text |Cite
|
Sign up to set email alerts
|

Joggobot

Abstract: Joggobot illustrates a novel approach towards a more social use of robots, where the robot acts as exercise companion to make physical activity more enjoyable. Joggobot is the first autonomous flying robot companion for joggers. Joggobot makes the solo running experience more enjoyable by flying next to you when jogging, offering a coach mode to motivate you to run faster and further, and a "looking after" mode that is similar to jogging with a dog. The results are more enjoyable runs, furthering the many phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies have sought to present alternatives for visually impaired athletes, such as the study reported in [18] that uses Goby, which is an auxiliary mechanism to provide audio feedback to swimmers (e.g., when the athlete is swimming outside the lane or is approaching the wall of the swimming pool). Moreover, the scientific literature presents studies that make use of controlled robots or drones to provide feedback to the athletes [19][20][21][22][23], voice assistants as an instrument to assist performance [24], portable personal navigation device that provided the current position and possible directions [25], or assistive technologies supported on location-based services [26].…”
Section: Problem and Foundationsmentioning
confidence: 99%
“…Some studies have sought to present alternatives for visually impaired athletes, such as the study reported in [18] that uses Goby, which is an auxiliary mechanism to provide audio feedback to swimmers (e.g., when the athlete is swimming outside the lane or is approaching the wall of the swimming pool). Moreover, the scientific literature presents studies that make use of controlled robots or drones to provide feedback to the athletes [19][20][21][22][23], voice assistants as an instrument to assist performance [24], portable personal navigation device that provided the current position and possible directions [25], or assistive technologies supported on location-based services [26].…”
Section: Problem and Foundationsmentioning
confidence: 99%